La Guerra de España en el contexto de la crisis internacional de entreguerras - David Jorge (Amnis)
The Spanish Civil War was the peak of the international crisis which marked the decade of the 1930’s all around the world. While it was in Manchuria (1931) where impunity began with an act of aggression by one sovereign state against another of its same condition (both of them members of the League of Nations), it was in Abyssinia (1935-1936) where the system of collective security was broken with the lifting of the sanctions initially imposed to Italy due to its attack and invasion of Ethiopia. In Spain (1936-1939), the non-resurrection of the international order emanated from Versailles originated a new world war. A coup not exempt from exogenous elements and which led to a dramatic balance of forces was followed by international war on Spanish soil, determined by the correlation of international interventions and retractions in a greater extent than by the national elements themselves. The Spanish conflict, which has sometimes been referred as « the last great cause », meant the end of Wilsonian idealism in the frame of international relations as well as the failure of the extraordinary path of social and cultural progress developed in Spain during its Edad de Plata.